Pengaruh Penerapan Metode Resitasi Terhadap Motivasi Belajar Siswa Kelas XI Akuntansi Pada Mata Pelajaran Akuntansi di SMK Negeri 4 Soppeng - Aris Munandar; M. Ridwan Tikollah; Nuraisyiah Nuraisyiah (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the effect of the application of the recitation method on the learning motivation of accounting class XI students in Accounting subjects at SMK Negeri 4 Soppeng. The population in this study is all Accounting grade XI students at SMK Negeri 4 Soppeng which totals 34 students, while the sample in this study was taken using the total sampling technique. The data collection techniques used are questionnaires and observation. The data analysis techniques used are percentage descriptive analysis, simple linear regression, and hypothesis testing using SPSS 27 for windows. The results of this study show that the variable of the recitation method has a positive and significant effect on the learning motivation of accounting students at SMK Negeri 4 Soppeng.